Seeking children's perspectives: a respectful layered research approach - Merewether, Jane; Fleet, A. (Routledge, 2013)
This article discusses why researchers and educators might choose to seek children's perspectives. It also highlights some of the key considerations when seeing children as having the right to contribute to decisions that affect them. The article draws on findings from a study that used pedagogically oriented methods for researching three- and four-year-old children's perspectives about outdoor spaces in the early childhood setting they attended. The article discusses the possibilities and practicalities of this research approach for both research and pedagogy. Examples are provided for others who may be considering working/researching in these ways.